Financing decisions and financial constraints: evidence from the UK and China - Kasseeah, Harshana (2008)
Firms are the engines of growth in any economy. It is therefore important to study how they finance themselves, as this may have a direct impact on the overall growth rate of the economy. A firm can choose whether to finance its activities with equity, debt, or both. An optimal capital structure is that mix of internal and external finance (debt and/or equity) that optimizes the value of a firm. Therefore, the question of how to finance or equivalently from where to borrow becomes a crucial decision.